Exposure to BMAA mirrors molecular processes linked to neurodegenerative disease. Issue 17 (24th August 2017) - Beri, Joshua; Nash, Tara; Martin, Rubia M.; Bereman, Michael S.
Abstract: The goal of this study is to investigate the molecular pathways perturbed by in vitro exposure of beta‐methylamino‐L‐alanine (BMAA) to NSC‐34 cells via contemporary proteomics. Our analysis of differentially regulated proteins reveals significant enrichment ( p < 0.01) of pathways related to ER stress, protein ubiquitination, the unfolded protein response, and mitochondrial dysfunction. Upstream regulator analysis indicates that exposure to BMAA induces activation of transcription factors (X‐box binding protein 1; nuclear factor 2 erythroid like 2; promyelocytic leukemia) involved in regulation of the UPR, oxidative stress, and cellular senescence. Furthermore, the authors examine the hypothesis that BMAA causes protein damage via misincorporation in place of L‐Serine. The authors are unable to detect misincorporation of BMAA into protein via analysis of cellular protein, secreted protein, targeted detection of BMAA after protein hydrolysis, or through the use of in vitro protein translation kits.